Formulation and Evaluation of Fluconazole Gel for Topical Application - Shelke, Suvarna; Deshmukh, Amol; Shinde, Prajakta; Dighe, Pravin (Asian Journal of Pharmaceutical Research and Development, 2021)
Objective: The development of topical gel formulation is needed because it offers an interesting alternative for oral route to achieving systemic and local effect of drug. Topical gel is having important advantages like avoid GI irritation, avoid first pass metabolism and increase the bioavailability of the drug. Fluconazole is a synthetic triazole antifungal drug used in the treatment and prevention of superficial and systemic fungal infection. Adverse effects reported with fluconazole most commonly affect the gastrointestinal tract and include abdominal pain, diarrhoea, flatulence, nausea and vomiting, and taste disturbance after oral administration. In order to bypass these disadvantages, the gel formulations have been proposed as topical application. Method: Topical gel was prepared using combination of Carbopol and guar gum. Evaluation of the topical gel of fluconazole was carried out for physical appearance, pH, Spreadability, Extrudability, Rheological studies, Drug content, antifungal activity, in vitro release, Ex- vivo permeation study and skin irritation study. Result: The varying concentrations of two polymers were found to affect the gel parameters like drug release, Spreadability and its viscosity. The accelerated stability studies were performed according to ICH guidelines for 3 months and the results were found to be stable in varying temperature.